Effect of oxidation stability on the fuel and storage properties of Balanites Aegyptiaca biodiesel - Usman, Abdulyakin; Ahmad Rufai, Ibrahim (Penerbit Universiti Kebangsaan Malaysia, 2021)
Biodiesel prepared from Balanites aegyptiaca oil, through transesterifcation process, has promising potentials for use as fuel for diesel engines. However, there is limited information regarding the physical and chemical stability of this biodiesel during storage. In view of the aforementioned, this study was carried out in order to determine the oxidation stability as well as the extent of deterioration of Balanites aegyptiaca biodiesel during storage. Storage stability study was carried-out for three (3) months with the view to investigate the effect of oxidation on the biodiesel. The induction period and storage stability parameters were determined in accordance with official standard methods. The Balanites aegyptiaca biodiesel was found to have an induction period of 66 minutes. The storage stability study shows that: the peroxide value increased from 1.4 mEq/kg to 9.4 mEq/kg; cetane number increased from 50.42 to 52.48; while acid value increased from 0.11 mgKOH/g to 0.36 mgKOH/g. In addition, changes were observed in: saponification value from 215.99 mgKOH/g to 220.19 mgKOH/g, kinematic viscosity from 4.7 mm2/sec to 5.0 mm2/sec at 40˚C and density from 887 kg/m3 to 897 kg/m3 at 15˚C. The iodine value and lower heating value decreases from 68.53 gI2/100g to 55.84 gI2/100g and from 37.5 MJ/kg to 36.2 MJ/kg respectively during the storage period. However, despite the variations observed during the storage, the parameters were still within the ASTM and European specification standards for biodiesel. The result suggests that the Balanites aegyptiaca biodiesel may be stored for up to three months without losing its fuel properties.